Comparison of surgical outcomes between lateral and posterior methods for retroperitoneoscopic adrenalectomy: insights from a single center’s experience - Que, Hongliang; Fan, Zhongru; Deng, Junpeng; Li, Quan; Zeng, Tengyue; Zhang, Qijie; Wang, Ke; Xie, Jianjun (Frontiers in Oncology, 2026)
PurposeLateral retroperitoneoscopic adrenalectomy (LRA) and posterior retroperitoneoscopic adrenalectomy (PRA) are both minimally invasive approaches for adrenal gland resection without entering the peritoneal cavity. Direct comparisons of their perioperative outcomes remain limited. This study evaluates the safety and efficacy of LRA versus PRA for adrenal tumor management.MethodsWe retrospectively analyzed data from 185 patients undergoing LRA (n=95) or PRA (n=90) at a single center between January 2018 and May 2023. The cohort had a mean age of 53.8 ± 13.0 years, BMI of 24.8 ± 3.27 kg/m², and 50.3% (n=93) were male. Median tumor diameter was 2.3 cm (range: 1.0–6.5 cm). Perioperative parameters, complications, and outcomes were compared between groups. Propensity score matching (PSM) method was used to balance the potential confounding variables.ResultsPRA demonstrated significantly shorter operative time (56.2 ± 13.7 vs. 79.0 ± 22.8 minutes; p < 0.001) and postoperative hospitalization (4.48 ± 1.50 vs. 5.91 ± 1.79 days; p < 0.001) compared to LRA. Hemoglobin change (1.32 ± 0.50 vs. 1.20 ± 0.28 g/dL; p = 0.060) and complication rates were comparable between groups. No cases required conversion to open surgery or resulted in mortality. PSM analysis validated the stability of these results. Multivariate logistic regression analysis indicated that BMI, being male, and the LRA approach were associated with operative time exceeding 60 minutes. Prolonged operative time and LRA were associated with extended hospital stays.ConclusionsBoth LRA and PRA are safe and effective for adrenal tumor resection. Meanwhile, PRA may offer superior efficiency, with reduced operative duration and hospitalization, suggesting its potential as the preferred approach in select patients.